Analisis Penyebab Kecelakaan Kerja dan Pengaruh Penggunaan Alat Pelindung Diri (APD) pada Pekerja Konstruksi di PT. Bagas Patih Pratama - Raisa Shabrina Batu Bara; Susilawati Susilawati (Lembaga Pengembangan Kinerja Dosen, 2024)
. The construction sector is a high-activity sector, making it prone to accident hazards. Therefore, safety analysis is useful for identifying and mitigating risk factors and potential causes of disruptions. Personal Protective Equipment (PPE) is one of the efforts to protect workers from the hazards of workplace accidents. The purpose of this occupational safety and health (OSH) study is to analyze the causes of workplace accidents and the impact of using Personal Protective Equipment (PPE) at PT. Bagas Patih Pratama to enhance employee safety and reduce accident risks in the workplace. The data collection technique in this study involves questionnaires or interviews with workers to gather the necessary information. This study evaluates workers' attitudes towards health and safety conditions, knowledge of safety protocols, and the challenges faced during work. The survey results show that the majority of workers have a high level of awareness and understanding of workplace safety and the importance of using Personal Protective Equipment (PPE). However, only a few workers consistently comply with established safety protocols. The study also highlights the importance of using Personal Protective Equipment (PPE) to reduce hazards when working. It is recommended that the company enhance safety training programs and closely monitor the use of PPE to minimize workplace accident risks in the future.